PERBANDINGAN BIAYA DESAIN PERKERASAN ASPAL DENGAN UMUR RENCANA PADA PROYEK JALAN BATAS KOTA CILEGON-CIBALIUNG DAN CITEREUP-TANJUNG LESUNG - Jimmy Nugroho; Darmadi (FTSP Universitas Jayabaya, 2019)
Roads are an important infrastructure in supporting economic development in an area. Good quality is prioritized for the safety and comfort of road users. Improvement of the Beru –Cinandang Road Section (STA 0 + 000 - 9 + 410), Pandegelang Regency consists of pavement thickness, and calculation of the budget plan. The methods used include Road Pavement Design Manual Number 02 / M / BM / 2013 and calculating the Cost Budget Plan using the Analysis of Work Unit Price (AHSP) for the Public Works Balitbang 2012 Public Works, from each of the pavement thickness planning results. The research data used include primary and secondary data from the Cilegon-Cibaliung City and Citereup-Tanjung Lesung Boundary Road Reconstruction project. The results of this study are road pavement planning with a road body width of 7 m, planning pavement thickness with Laston and Asbuton with Laston Layer 4 cm thick, Laston layer between AC-BC 6 cm thick, Laston AC Base base layer 16 thick with top foundation in the form of stone broke the class A 30 cm along with the bottom foundation of the selected heap with a thickness of 30 cm and calculated the Comparison of the Budget Plan for 20,989,956,000.